An Investigation Into the Mechanism of Rock Bursts in Mines for Tunnel-Cut Isolated Areas with Multiple Stress Fields - Zhang, Heng; Ouyang, Zhenhua; Li, Tie; Liu, Su; Yi, Haiyang; Wang, Honglei; Chen, Jianqiang; Li, Kang (Frontiers in Earth Science, 2022)
Abstract: Tunnels in several mines in Shaanxi Province, China, which are subject to multiple stress fields, are used as case studies to clarify the structural problems associated with rock bursts that occur in high-stress mines. Field studies featuring field measurements and theoretical analysis are used to investigate the modes and mechanisms of failure. The following are the main findings: (1) a model for distributing the dominant pressure features around the goaf was established by analyzing the stress distribution induced by the goafs on both sides of the excavated zone in a coal seam. The model reveals the pressure distribution in the tunnel-cut area, which is the mechanical factor responsible for rockburst. (2) Because of the goafs acting on both sides of the tunnel, an area of concentrated stress was formed, and stress was transferred to the coal seam. The intense tunnel-cutting action can reduce the stability of the coal. The plastic area caused by tunnel mining and a reduction in the elastic area of the tunnel-cut coal pillars in each segment, increase the possibility for rockburst under the application of dynamic-static stress; this process is known as a stabilizing factor. (3) Due to the combined effect of the tunnel-cut and goafs on both sides, most of the microseismic incidents happened in the core area of coal pillar and in the side of tunnels. When the stress applied on coal pillar is more than critical strength, burst and mine earthquake can be induced. Our study focused mainly on rockburst incidents that occurred in coal mines in Shaanxi Province, which were caused by tunnel-cut coal seams that were subject to multiple stress fields. The study has direct implications for developing new and improved guidelines for preventing rockburst in mines.